(3ebGdI aj GdMeis - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s ((3Ydi Hf EHQGgje Hf CMeO GdJLjHi s)
(3ChdgG (B:s
(3bO jLH Cf jYJbO Cf ReGf GdfhHI gh aYd GdMQGQI GdZQjRjI ai LRA ef GdNdW GdaGYd dMei MJi jgVe efgG eG gVeJ s
(3BNQgG (B:s
(3hCeG GdMei GdOGFeI agi GdJi YahfJgG ai ehGVY GdgVe GdKdGKI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B64 - (3U(B65s
(3GfXQgG eY JdNjU cJGH GdMejGJ Qbe (B" 423"s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B313s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B245 s
Keywords: (3GdWHs